Quantifying the functional disparity in pigment spot-background egg colour ICP-OES-based eggshell ionome at two extremes of avian embryonic development - Grzegorz Orłowski (Nature Portfolio, 2020)
Abstract It is known that a developing avian embryo resorbs micronutrients (calcium and other chemical elements) from the inner layer of the eggshell, inducing thinning and overall changes in the shell’s chemical composition. However, an aspect yet to be explored relates to the local changes in the multi-elemental composition (ionome) of the pigment spot and adjacent background colour regions of eggshells resulting from avian embryogenesis (with respect to two extremes of embryonic growth: the maternal level at the moment of egg laying, and after the completion of embryonic growth). To address this problem, we used inductively-coupled plasma optical emission spectrometry (ICP-OES) to establish the elemental profiles of microsamples from the cryptic eggs of Capercaillie Tetrao urogallus and Black Grouse Tetrao tetrix, representing the background colour and pigment spot regions of the shell. We then related these to the developmental stage of the eggs (non-embryonated eggs vs. post-hatched eggshells) and their origin (wild vs. captive hens). Our results show an apparent local disparity between the pigment spot and background colour regions in the distribution of chemical elements: most elements tended to be at higher levels in the speckled regions of the shell, these differences becoming less pronounced in post-hatched eggshells. The trends of changes following embryonic eggshell etching between the pigment spot and background colour shell regions were conflicting and varied between the two species. We hypothesized that one potential working explanation for these interspecific differences could be based on the variable composition of elements (mostly of Ca and Mg), which are the result of the varying thickness of the individual shell layers, especially as the relative difference in shell thickness in the pigment spots and background colour regions was less in Black Grouse eggs. Overall, this investigation strongly suggests that egg maculation plays a functional role in the physiological deactivation of trace elements by incorporating them into the less calcified external shell layer but without participating in micronutrient resorption. Our major critical conclusion is that all research involving the chemical analysis of eggshells requires standardized eggshell sampling procedures in order to unify their colouration and embryonic status.